Kerukunan Antara Umat Beragama Dalam Masyarakat Madani (Analisi Piagam Madinahdan Relevansinya Bagi Indonesia) - Nur Ahsan (TASAMUH: Jurnal Studi Islam, 2015)
This study is a content analysis on existing clauses in the Charter of Medina. The results showed that Charter of Medina strictly regulated harmony among religious communities which did not restricted to Muslims only internally, but also between the Muslim communities with other people. From the articles of the Charther of Medina, it seems that the Prophet Muhammad gave a guarantee to all the people of Medina to perform their religious activities. Harmony of religious life in Indonesia, in principle, is set properly. The emergence of various conflicts between religious communities had been driven more by too little awareness among religious communities to adhere to the existing rules. There is a significant relevance if Indonesia now try to build a civil society based on civil values that had been practiced by the Prophet Muhammad in Medina.